Glutamine sustains energy metabolism and alleviates liver injury in burn sepsis by promoting the assembly of mitochondrial HSP60-HSP10 complex via SIRT4 dependent protein deacetylation - Yongjun Yang; Qian Chen; Shijun Fan; Yongling Lu; Qianyin Huang; Xin Liu; Xi Peng (Taylor & Francis Group, 2024)
ABSTRACTBurns and burn sepsis, characterized by persistent and profound hypercatabolism, cause energy metabolism dysfunction that worsens organ injury and systemic disorders. Glutamine (Gln) is a key nutrient that remarkably replenishes energy metabolism in burn and sepsis patients, but its exact roles beyond substrate supply is unclear. In this study, we demonstrated that Gln alleviated liver injury by sustaining energy supply and restoring redox balance. Meanwhile, Gln also rescued the dysfunctional mitochondrial electron transport chain (ETC) complexes, improved ATP production, reduced oxidative stress, and protected hepatocytes from burn sepsis injury. Mechanistically, we revealed that Gln could activate SIRT4 by upregulating its protein synthesis and increasing the level of Nicotinamide adenine dinucleotide (NAD+), a co-enzyme that sustains the activity of SIRT4. This, in turn, reduced the acetylation of shock protein (HSP) 60 to facilitate the assembly of the HSP60-HSP10 complex, which maintains the activity of ETC complex II and III and thus sustain ATP generation and reduce reactive oxygen species release. Overall, our study uncovers a previously unknown pharmacological mechanism involving the regulation of HSP60-HSP10 assembly by which Gln recovers mitochondrial complex activity, sustains cellular energy metabolism and exerts a hepato-protective role in burn sepsis.